Mediating effect of the normalised difference vegetation index between PM2.5 and its components and cardiovascular disease: evidence from CHARLS - Yong Wu; Liyun Wang; Weiling Liu; Weiqi Liu; Junhao Zhang; Huanjin Zhu; Keng Lin; Jiangxia Qin (BMJ Open, 2025)
Objectives To investigate the associations between fine particulate matter (PM2.5) and its components and cardiovascular disease (CVD) and to explore the potential mediating role of the normalised difference vegetation index (NDVI) in mitigating PM2.5 exposure and its related health risks.Design and setting Using data from the 4th and 5th waves of the China Health and Retirement Longitudinal Study, we included 11 279 eligible participants after strict screening.Methods A logistic regression model was used to assess the effects of PM2.5 and its components on CVD. The logistic regression, combined with restricted cubic splines, was used to explore non-linear associations, and a mediation analysis was performed to assess the role of the NDVI.Results Among the 11 279 participants, 775 (14.7%) developed CVD during the follow-up period. The results revealed that every 1 µg/m³ increase in the PM2.5 concentration was associated with a 2.1% (95% CI: 1.013 to 1.029) increased risk of CVD, and the sulphate, ammonium, nitrate, organic matter and black carbon components of PM2.5 also exhibited significant positive correlations. Mediation analysis revealed that the NDVI significantly mediated the effects of PM2.5 and its components on CVD, with mediation proportions ranging from 42.27% to 56.13%. Stratified analyses revealed significant interactions of PM2.5 and its components with CVD risk in different settlement types.Conclusions Exposure to PM2.5 and its constituents increases the risk of CVD. Increasing green space may help mitigate the adverse effects of air pollution on cardiovascular health, particularly in different types of settlements.